Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.477
|View full text |Cite
|
Sign up to set email alerts
|

Words are the Window to the Soul: Language-based User Representations for Fake News Detection

Abstract: Cognitive and social traits of individuals are reflected in language use. Moreover, individuals who are prone to spread fake news online often share common traits. Building on these ideas, we introduce a model that creates representations of individuals on social media based only on the language they produce, and use them to detect fake news. We show that language-based user representations are beneficial for this task. We also present an extended analysis of the language of fake news spreaders, showing that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Further work has shown that communities with more distinct words better retain users (Zhang et al, 2017), and tend to be smaller, denser, more active, and have more local engagement (Lucy and Bamman, 2021). Similar findings have been shown for communities with distinct word senses (Del Tredici and Fernández, 2017;Lucy and Bamman, 2021). We extend computational sociolinguistic work on community identity and engagement patterns by motivating and investigating variation of a different kind: variation in higher level properties of stancetaking.…”
Section: Related Worksupporting
confidence: 60%
“…Further work has shown that communities with more distinct words better retain users (Zhang et al, 2017), and tend to be smaller, denser, more active, and have more local engagement (Lucy and Bamman, 2021). Similar findings have been shown for communities with distinct word senses (Del Tredici and Fernández, 2017;Lucy and Bamman, 2021). We extend computational sociolinguistic work on community identity and engagement patterns by motivating and investigating variation of a different kind: variation in higher level properties of stancetaking.…”
Section: Related Worksupporting
confidence: 60%
“…For example, fake news is proven empirically to influence the 2016 U.S. presidential election (Bovet and Makse, 2019;Grinberg et al, 2019;Budak, 2019). Given the impact of false information, previous studies paid a lot of effort to detect it from different aspects, including (1) news content only (Santos et al, 2020;Kim and Ko, 2021), (2) the combination of news articles and social media replies Lu and Li, 2020), and (3) additional publisher/user information (Long et al, 2017;Yuan et al, 2020;Del Tredici and Fernández, 2020). In this work, we focus on using both news contents and social media replies, and further add external knowledge to enhance the model's ability to capture critical entities.…”
Section: Introductionmentioning
confidence: 99%